Childhood constipation and diet. Issue 4 (August 2009) - Inan, Mustafa
Constipation is a common problem in children. However, there is much controversy surrounding the etiology, diagnosis and treatment of functional constipation observed in childhood. Despite the high frequency of this problem documented in the literature, there is little research that assesses the direct relationship between the food consumed and the eventual stool consistency. Breastfeeding is an excellent way to prevent constipation in infants and toddlers, as is fruit and vegetable consumption in older children. The aim of this review is to investigate available tools in the literature concerning constipation in children and to discuss the relationship between constipation and diet in childhood.